Imaging and engineering optical localized modes at the nanoscale - Caselli, Niccolò (Premio Tesi di Dottorato, 2016)
In this thesis we experimentally developed high-resolution groundbreaking imaging techniques and novel methods suitable for nanophotonics materials. The experimental results are carefully supported by theory and numerical calculations. We engineered the propagation of light by exploiting devices that strongly localize electromagnetic fields at the nanoscale. The proposed techniques have a large field of application. We deeply investigated ordered and disordered based single and coupled nano-resonators, called photonicmolecules, and develop a laser-assisted local oxidation of the dielectric environment. These results put the basis for an unprecedented investigation of light behaviour in optical nano-resonators. Therefore, they would pave the way for novel devices that exploit the strong coupling regime between single light emitters and localized optical modes.